2014
DOI: 10.1063/1.4895195
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of goat's milk from three different locations in Malaysia

Abstract: Abstract. This study was conducted to evaluate the antioxidant activities of two types of goat milk obtained from three different farms in Malaysia named: Semenyih, Johor Baharu and Bander Baru Bangi . Milk from Jamnupari goat breed and a crossbred of Jamnupari and Saanen were investigated in terms of antioxidant capacity based on total phenol content (TPC), ferric reducing antioxidant power (FRAP), and 2,2-diphenyl-1-picrylhydrazyl (DPPH). Goat milk samples exhibited a significantly different antioxidant capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
1
5
0
1
Order By: Relevance
“…Also, correlation between milk fat content and antioxidant activity of milk was reported by Chen et al, [13]. Our results are consistent with the previous studies in human milk [14,15] and in goat milk [16] where they have reported that the total antioxidant capacity of milk had significantly higher values for colostrum as compared to mature and transitional milk. Colostrums milk could help in improving the antioxidant system to newborns.…”
Section: Tac By Frap Assaysupporting
confidence: 92%
“…Also, correlation between milk fat content and antioxidant activity of milk was reported by Chen et al, [13]. Our results are consistent with the previous studies in human milk [14,15] and in goat milk [16] where they have reported that the total antioxidant capacity of milk had significantly higher values for colostrum as compared to mature and transitional milk. Colostrums milk could help in improving the antioxidant system to newborns.…”
Section: Tac By Frap Assaysupporting
confidence: 92%
“…Several previous studies have reported that heat treatment reduced the radical scavenging activities of milk [ 18 ]. Casein has an effective role against lipid peroxidation and in radical scavenging activity [ 7 , 8 , 19 ]. Micellar casein is denatured during heating; therefore, the radical scavenging activity of heat-treated milk is reduced compared to non-treated milk.…”
Section: Discussionmentioning
confidence: 99%
“…En sistemas de libre pastoreo las dietas ricas en plantas con altos contendidos de fenoles son incorporados a la leche (Cabiddu et al, 2019). Los compuestos fenólicos ayudan a proporcionar actividad antioxidante a los productos derivados de la leche y mejoran la salud animal (Alyaqoubi et al, 2014;Reyes-Becerril et al, 2021). Dentro de otras alternativas para adicionar fenoles se encuentra la incorporación de Acacia farmesiana, Chlorella pyrenoidos y Origanum vulgare spp.…”
Section: Discussionunclassified